2020
DOI: 10.1002/jac5.1329
|View full text |Cite
|
Sign up to set email alerts
|

Global contributions of pharmacists during the COVID‐19 pandemic

Abstract: Throughout the SARS‐CoV‐2 (COVID‐19) global pandemic, pharmacists were rarely mentioned as essential frontline health care providers by the news media, the public, or politicians. Around the world, pharmacists are working on the frontlines of health care every day providing essential health care services during the pandemic. Pharmacists are medication experts providing patient care in a variety of settings including hospitals, clinics, community pharmacies, long‐term care, physician offices, and national and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 24 publications
0
55
0
2
Order By: Relevance
“…12,15,16,[36][37][38][39][40] Pharmacists as primary healthcare providers help them not only with primary health problems but also share reliable information on SARS-CoV-2. 15,37,[40][41][42][43][44] The National Community Pharmacists Association, which represents 21,000 pharmacies in the US, is launching a campaign with the intention of drawing people's attention to unknown heroes. The founders want to make people aware that the community can rely on local pharmacists to gain excellent knowledge, consultation and commitment appropriate for neighbors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,15,16,[36][37][38][39][40] Pharmacists as primary healthcare providers help them not only with primary health problems but also share reliable information on SARS-CoV-2. 15,37,[40][41][42][43][44] The National Community Pharmacists Association, which represents 21,000 pharmacies in the US, is launching a campaign with the intention of drawing people's attention to unknown heroes. The founders want to make people aware that the community can rely on local pharmacists to gain excellent knowledge, consultation and commitment appropriate for neighbors.…”
Section: Resultsmentioning
confidence: 99%
“…Despite minor misunderstandings regarding the duties and competences of both professions, mutual communication and trust are the keys to success. 38,42,63 Both professions believe that the most important barriers in doctor-pharmacist cooperation are: lack of time, no fixed salary, no direct communication and agreement, and no clear division and definition of responsibilities. 64 It is worth noting that doctors who have previously cooperated with a pharmacist are more supportive of further collaboration.…”
mentioning
confidence: 99%
“…In the midst of the COVID-19 pandemic, there are increasing calls for pharmacists to play a more active role in the public health response, beyond dispensing of medicines and other supplies. In particular, it has been suggested that in the context of pandemics, pharmacists could be involved in outbreak surveillance, 1 , 2 , 3 , 4 , 5 , 6 health education, 7 drug trials, 8 vaccine delivery, 9 testing, 10 and programs to support patient medication adherence. 11 These roles become critical when clinical services are heavily committed, especially in countries where health systems are under-resourced.…”
Section: Introductionmentioning
confidence: 99%
“…Several independent studies endorsed pharmacists’ perception of their willingness and preparedness in fighting the COVID-19 pandemic [ 12 , 13 ]. Goff, Debra A. et al discussed international efforts of pharmacists in nine countries by providing crucial frontline care to COVID-19 patients in different settings, including: hospitals, community pharmacies, clinics, long-term care, physician offices, nursing homes, and national and public health [ 21 ].…”
Section: Discussionmentioning
confidence: 99%